Evaluación experimental de la toxicidad de infusiones comerciales de muña y mate de coca mediante el crecimiento radicular de Allium cepa - Quispe Llanos, Braulio (2026)
Objective: To assess the acute toxicity of commercial muña (Minthostachys mollis) and coca leaf (Erythroxylum coca) infusions using the standardized Allium cepa (A. cepa) bioassay. Materials and methods: A randomized experimental study was conducted. Thirty-three A. cepa bulbs were randomly distributedinto 11 experimental groups (n = 3). The specimens were exposed for 12 days to infusions prepared daily at graded concentrations (10 %, 25 %, 50 %, 75 %, and 100 %), with distilled water as a negative control. The solutions were systematically renewed every 24 hours under controlled environmental conditions of darkness and temperature (20–25 °C). Root length was measured at multiple time points (days 3, 5, 8, 10, and 12), and changes in fresh bulb weight were recorded; results were expressed as percentages of inhibition. Statistical analysis was performed using SPSS version 27 and GraphPad Prism. The study included analysis of variance (ANOVA), Tukey’s HSD post hoc test, Pearson correlation, and nonlinear regression to calculate the half-maximal inhibitory concentration (IC50). Results: Exposure to muña infusion showed a dose-dependent inhibition of root growth (p < 0.001), reaching a maximum value of 92.16 % on day 12 (100% concentration). A strong positive correlation was observed (r = 0.95; p < 0.0001) and the IC50 was estimated at 42.51 % (95 % CI: 37.51–48.19).  Incontrast, coca leaf infusion  causedstatistically significant inhibition at all concentrations (maximum of 80.03 % at 75 %); the IC50 could not be estimated due to high toxicity (> 50 % inhibition at all concentrations). Regarding biomass, muña at 100 % caused a significant weight loss (Δ = −4.1 g), compared with the weight gain observed in the control group (Δ = 23.5 g; p < 0.01). Conclusions: The commercial muña and coca leaf infusions analyzed exhibited marked toxicity in the A. cepa model, limiting root growth and altering weight. These findings warn of the risks associated with indiscriminate consumption and support the need for further complementary safety studies inmammalian cell models to evaluate safety for human use.